2020
DOI: 10.1172/jci140311
|View full text |Cite
|
Sign up to set email alerts
|

Functional α6β4 acetylcholine receptor expression enables pharmacological testing of nicotinic agonists with analgesic properties

Abstract: The authors are all full-time employees of Janssen Pharmaceutical Companies of Johnson and Johnson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…The dorsal root ganglia (DRG) play a role in nociception and coexpress α6 and β4 mRNA (23). Consistent with the experiments performed in HEK293T cells, wild-type DRG neurons had greater α6β4 surface levels than BARP-KO neurons (17). Nicotine has an antiallodynic effect in rodent models of neuropathic pain (24).…”
Section: The Analgesic Target For Epibatidine Has Posed Challengessupporting
confidence: 75%
See 4 more Smart Citations
“…The dorsal root ganglia (DRG) play a role in nociception and coexpress α6 and β4 mRNA (23). Consistent with the experiments performed in HEK293T cells, wild-type DRG neurons had greater α6β4 surface levels than BARP-KO neurons (17). Nicotine has an antiallodynic effect in rodent models of neuropathic pain (24).…”
Section: The Analgesic Target For Epibatidine Has Posed Challengessupporting
confidence: 75%
“…The authors found no difference between nicotine's antiallodynia properties in NACHO-KO mice compared to wild-type mice, consistent with the paper's viewpoint that α6β4 is the nAChR that carries out nicotine's antiallodynia effects. Inhibition of α4β2 did not prevent nicotine-induced antiallodynia (17).…”
Section: The Analgesic Target For Epibatidine Has Posed Challengesmentioning
confidence: 77%
See 3 more Smart Citations